High-Yield Production of a Rich-in-Hydroxytyrosol Extract from Olive (Olea europaea) Leaves - Costas S. Papageorgiou; Paraskevi Lyri; Ioanna Xintaropoulou; Ioannis Diamantopoulos; Dimitris P. Zagklis; Christakis A. Paraskeva (MDPI AG, 2022)
The aim of the present study was to explore the high-yield production of hydroxytyrosol, a phenolic compound with very high antioxidant capacity. Olea europaea leaves were chosen as feedstock as they contain significant amounts of oleuropein, which can be hydrolyzed to hydroxytyrosol. The chosen techniques are widely used in the industry and can be easily scaled up. Olive leaves underwent drying and mechanical pretreatment and extractives were transported to a solvent by solid-liquid extraction using water-ethanol mixtures. The use of approximately 60-80% ethanol showed an almost 2-fold increase in extracted phenolics compared to pure water, to approximately 45 g/kg of dry leaves. Extracted oleuropein was hydrolyzed with hydrochloric acid and the hydrolysate was extracted with ethyl acetate after pH adjustment. This step led to a hydroxytorosol content increase from less than 4% to approximately 60% w/w of dry extract, or 10-15 g of hydroxytyrosol recovery per kg of dry leaves.